SOX2 Targets Fibronectin 1 to Promote Cell Migration and Invasion in Ovarian Cancer: New Molecular Leads for Therapeutic Intervention - Lou, Xiaoyan (Mary Ann Liebert, Inc., 2013)
Ovarian cancer ranks as the second most common tumor of the female reproductive system, with a large burden on global public health. Therefore, the identification of novel molecular targets and diagnostics is an urgent need for many women affected by this disease. To this end, the human transcription factor SOX2 is involved in a wide range of pathophysiological roles, such as the maintenance of stem cell characteristics and carcinogenesis. To date, in most studies, SOX2 has been shown to promote the development of cancer, although its inhibitory roles in cancer have also been reported. However, to the best of our knowledge, the role of SOX2, specifically in ovarian cancer cells, has not been examined in detail. In this article, we report, for the first time, that SOX2 promotes migration, invasion, and clonal formation of ovarian cancer cells. We further observed that SOX2 targeted FN1, a key gene that regulates cell migration in ovarian cancer. Our findings collectively suggest that the SOX2-FN1 axis is a key pathway in mediating the migration and invasion of ovarian cancer cells. This pathway offers crucial molecular insights and promises to develop putative candidate therapeutic interventions in women with ovarian cancer.